Effects of 15-year straw incorporation on soil carbon composition and microbial community under wheat–maize rotation system in the Huang-Huai-Hai Plain - Xiang Chen; Zhiwei Tang; Ying Weng; Hongmei Cai; Yu Wu; Baoqiang Zheng; Jincai Li (BMC Plant Biology)
Abstract Background Straw incorporation is an effective agronomic practice for improving soil fertility and crop yield. In this study, we investigated the effects of the different straw incorporation modes on soil organic carbon components, enzyme activities, and microbial community in the Vertisols of the Huang-Huai-Hai Plain based on a 15-year field experiment. In detail, four straw incorporation modes were carried out, control without straw incorporation (CK), crushed wheat straw mulching in summer maize season (T1), crushed wheat straw mulching in summer maize season and crushed maize straw was buried in winter wheat season (T2), crushed maize straw was buried in winter wheat season (T3). Results Results showed that all straw incorporation modes significantly increased SOC in both the wheat and maize season soil, with T2 having the greatest effect on boosting SOC. Straw incorporation modes increased soil labile organic carbon components, T2 and T3 significantly elevated DOC by 60.1% and 64.3%, respectively. Straw incorporation also increased the activities of αG, βG, CBH, βX, NAG, LAP, and AP. In both wheat and maize season soil, T2 significantly increased LAP activity by 119.0% and 127.4%, respectively. Furthermore, we found that although crushed wheat straw mulching in the summer maize season could effectively increase the diversity of microbial communities in the short term, it did not improve the long-term stability of the soil microbial community in the wheat-maize rotation system. Conclusion These results suggest that crushed wheat straw mulching in summer maize season and crushed maize straw was buried in winter wheat season (T2) can be an effective strategy to improve soil labile organic carbon components, enzyme activities, and the ecological function of microbial community in the Vertisols of the Huang-Huai-Hai Plain.